2024
DOI: 10.1038/s41586-024-07093-w
|View full text |Cite
|
Sign up to set email alerts
|

The UFM1 E3 ligase recognizes and releases 60S ribosomes from ER translocons

Linda Makhlouf,
Joshua J. Peter,
Helge M. Magnussen
et al.

Abstract: Stalled ribosomes at the endoplasmic reticulum (ER) are covalently modified with the ubiquitin-like protein UFM1 on the 60S ribosomal subunit protein RPL26 (also known as uL24)1,2. This modification, which is known as UFMylation, is orchestrated by the UFM1 ribosome E3 ligase (UREL) complex, comprising UFL1, UFBP1 and CDK5RAP3 (ref. 3). However, the catalytic mechanism of UREL and the functional consequences of UFMylation are unclear. Here we present cryo-electron microscopy structures of UREL bound to 60S rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…A major substrate for UFMylation is the 60S ribosomal subunit RPL26, which occurs on stalled ribosomes at the ER. Structural evidence suggests the role of UFM1 modification in this context is to release 60S ribosomes from the SEC61 translocon to regulate protein homeostasis at the ER [ 269 , 270 ]. UFM1 substrates have additionally been identified that have roles in DDR signalling and telomere maintenance pathways, including MRE11 [ 271 ] and histone H4 [ 272 ].…”
Section: Ulps In Genome Stabilitymentioning
confidence: 99%
“…A major substrate for UFMylation is the 60S ribosomal subunit RPL26, which occurs on stalled ribosomes at the ER. Structural evidence suggests the role of UFM1 modification in this context is to release 60S ribosomes from the SEC61 translocon to regulate protein homeostasis at the ER [ 269 , 270 ]. UFM1 substrates have additionally been identified that have roles in DDR signalling and telomere maintenance pathways, including MRE11 [ 271 ] and histone H4 [ 272 ].…”
Section: Ulps In Genome Stabilitymentioning
confidence: 99%